Controlling the interfacial reactions and environment of rare-earth ions in thin oxide films towards wafer-scalable quantum technologies. Issue 1 (1st November 2021) - Harada, N.; Tallaire, A.; Serrano, D.; Seyeux, A.; Marcus, P.; Portier, X.; Labbé, C.; Goldner, P.; Ferrier, A.
Abstract : Encapsulating the active layer containing rare-earth ions between undoped thick layers allows limiting interfacial reactions during thermal annealing and leads to narrower homogeneous and inhomogeneous linewidths. Abstract : Rare earth (RE) doped oxides have demonstrated great potential for photonic applications and have also appeared as promising candidates for quantum memory devices and microwave to optical transducers. Here, we investigate the potential of Chemical Vapor Deposited (CVD) europium-doped Y2 O3 thin films on silicon as a new platform for integrated quantum devices. We aim at improving the optical properties of such thin films by carefully controlling the RE ion's environment. In particular, we study the effect of annealing post treatments and demonstrate that a significant source of broadening of the optical transition arises from interfacial reactions with the silicon substrate. We thus propose to encapsulate RE ions between undoped high-quality thick layers in order to limit the impact of interfacial reactions on their properties during thermal annealing. Using this approach, we succeeded in measuring a narrow inhomogeneous linewidth of 18 GHz and an ultra-narrow homogeneous linewidth of 5 MHz inferred from spectral hole width. These results are promising towards the use of these engineered RE doped thin films for the development of a scalable nanostructured spin-photon interface. In addition, our strategy could be applied to a large variety of oxide films for a broad range of applications.